Golgi-located NTPDase1 of Leishmania major is required for lipophosphoglycan elongation and normal lesion development whereas secreted NTPDase2 is dispensable for virulence. - Fiona M Sansom; Julie E Ralton; M Fleur Sernee; Alice M Cohen; David J Hooker; Elizabeth L Hartland; Thomas Naderer; Malcolm J McConville (Public Library of Science (PLoS), 2014)
Parasitic protozoa, such as Leishmania species, are thought to express a number of surface and secreted nucleoside triphosphate diphosphohydrolases (NTPDases) which hydrolyze a broad range of nucleoside tri- and diphosphates. However, the functional significance of NTPDases in parasite virulence is poorly defined. The Leishmania major genome was found to contain two putative NTPDases, termed LmNTPDase1 and 2, with predicted NTPDase catalytic domains and either an N-terminal signal sequence and/or transmembrane domain, respectively. Expression of both proteins as C-terminal GFP fusion proteins revealed that LmNTPDase1 was exclusively targeted to the Golgi apparatus, while LmNTPDase2 was predominantly secreted. An L. major LmNTPDase1 null mutant displayed increased sensitivity to serum complement lysis and exhibited a lag in lesion development when infections in susceptible BALB/c mice were initiated with promastigotes, but not with the obligate intracellular amastigote stage. This phenotype is characteristic of L. major strains lacking lipophosphoglycan (LPG), the major surface glycoconjugate of promastigote stages. Biochemical studies showed that the L. major NTPDase1 null mutant synthesized normal levels of LPG that was structurally identical to wild type LPG, with the exception of having shorter phosphoglycan chains. These data suggest that the Golgi-localized NTPase1 is involved in regulating the normal sugar-nucleotide dependent elongation of LPG and assembly of protective surface glycocalyx. In contrast, deletion of the gene encoding LmNTPDase2 had no measurable impact on parasite virulence in BALB/c mice. These data suggest that the Leishmania major NTPDase enzymes have potentially important roles in the insect stage, but only play a transient or non-major role in pathogenesis in the mammalian host.